2017
DOI: 10.4103/0972-9062.217617
|View full text |Cite
|
Sign up to set email alerts
|

Computer-aided analysis of phytochemicals as potential dengue virus inhibitors based on molecular docking, ADMET and DFT studies

Abstract: Five out of nine phytochemicals are reported for the first time as novel DENV inhibitors. These included three phytochemicals from Silybum marianum, i.e. Derrisin, Mundulinol, Isopomiferin, and two phytochemicals from Fumaria indica, i.e. Narlumicine and Oxysanguinarine. However, all the nine phytochemicals can be considered for in vitro and in vivo analysis for the development of potential DENV inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Using in silico drug development approach against the dengue nonstructural protein 4B (NS4B), Qaddir et al docked 2750 phytochemicals from different medicinal plants to the DENV NS4B protein and identified nine phytochemicals possessing potential inhibitory effects against NS4B, including silibinin and other compounds from the plant S. marianum [18]. This result suggests that silibinin could potentially inhibit DENV viral replication.…”
Section: Antiviral Activity Of Silymarin and Its Derivatives In VImentioning
confidence: 99%
“…Using in silico drug development approach against the dengue nonstructural protein 4B (NS4B), Qaddir et al docked 2750 phytochemicals from different medicinal plants to the DENV NS4B protein and identified nine phytochemicals possessing potential inhibitory effects against NS4B, including silibinin and other compounds from the plant S. marianum [18]. This result suggests that silibinin could potentially inhibit DENV viral replication.…”
Section: Antiviral Activity Of Silymarin and Its Derivatives In VImentioning
confidence: 99%
“…Recently, silymarin and baicalein were reported to be potent antiviral agents against EV-A71 12 . Previous in silico studies showed silymarin can able to inhibit DENV NS4B with a binding affinity of more than − 8 kcal/mol 20 . However, not much is known about the antiviral properties of silymarin, baicalein, and baicalin against all four dengue serotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Silymarin's antiviral effects have been studied in viruses such as HCV, influenza A virus, mayaro virus (MAYV), chikungunya virus (CHIKV), and human immunodeficiency virus (HIV). Silymarin has antiviral activity against all of the viruses mentioned, preventing virus entry into host cells, genomic content replication, and viral protein gene expression 27 . A review of the preventive capability of Silymarin is reviewed elsewhere 28…”
Section: Discussionmentioning
confidence: 99%